Assessment of Metabolic Syndrome in Patients with Chronic Obstructive Pulmonary Disease: A 6-Month Follow-Up Study - Elena-Andreea Moaleș; Lucia Corina Dima-Cozma; Doina-Clementina Cojocaru; Ioana Mădălina Zota; Cristina Mihaela Ghiciuc; Cristina Andreea Adam; Mitică Ciorpac; Ivona Maria Tudorancea; Florin Dumitru Petrariu; Maria-Magdalena Leon; Romică Sebastian Cozma; Florin Mitu (Diagnostics)
Background/Objectives: The association between chronic obstructive pulmonary disease (COPD) and metabolic syndrome (MetS) is a common one, with long-term therapeutic and prognostic impact. In view of the high pulmonary and cardiovascular morbidity and mortality, self-management contributes to decreasing the risk of an acute cardiac event or pulmonary decompensation. Methods: We conducted a prospective cohort study on 100 patients admitted to Iasi Clinical Rehabilitation Hospital who were divided into two groups according to the presence (67 patients) or absence (33 patients) of MetS. All patients benefited from multidisciplinary counseling sessions on their active role in improving modifiable cardiovascular risk factors and thus increasing quality of life. The aim of this study was to examine the impact of metabolic syndrome on lung function and the role of self-management in a 6-month follow-up period. The demographic, anthropometric, cardiovascular risk factors, and respiratory function were analyzed at baseline and at 6 months. Results: The presence of MetS was associated with higher fasting blood glucose (p = 0.004) and triglycerides (p = 0.003) but not with higher levels of interleukins or TNF-alpha. At the 6-month follow-up, abdominal circumference, forced expiratory volume in one second (FEV1), dyspnea severity, and blood pressure values improved in male patients with COPD. Systolic and diastolic blood pressure decreased in the COPD group as a whole, but especially in male patients with and without associated MetS. BMI was positively correlated with FEV1 (r = 0.389, p = 0.001) and the FEV1/forced vital capacity (FVC) ratio (r = 0.508, p < 0.001) in all COPD patients and in the MetS subgroup. In the COPD group as a whole. the six-minute walk test (6MWT) results (m) were positively correlated with FEV1 and FVC. The correlation remained significant for FVC in COPD patients with and without MetS. An increase in BMI by one unit led to an increase in TG values by 3.358 mg/dL, and the presence of metabolic syndrome led to an increase in TG values by 17.433 mg/dL. Conclusions: In our study, MetS is a common comorbidity in patients with COPD and is associated with higher BMI, fasting glucose, and triglycerides but not with the inflammatory parameters. A mixed pulmonary–cardiovascular rehabilitation intervention leads to improvement in various parameters in both female and male COPD patients.